2010
DOI: 10.1073/pnas.0812851107
|View full text |Cite
|
Sign up to set email alerts
|

Competing feedback loops shape IL-2 signaling between helper and regulatory T lymphocytes in cellular microenvironments

Abstract: Cytokines are pleiotropic and readily diffusible messenger molecules, raising the question of how their action can be confined to specific target cells. The T cell cytokine interleukin-2 (IL-2) is essential for the homeostasis of regulatory T (Treg) cells that suppress (auto) immunity and stimulates immune responses mediated by conventional T cells. We combined mathematical modeling and experiments to dissect the dynamics of the IL-2 signaling network that links the prototypical IL-2 producers, conventional T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
303
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(315 citation statements)
references
References 39 publications
12
303
0
Order By: Relevance
“…For example, the activation of individual T cells does not occur homogeneously upon stimulation-even isogenic ones-but rather activate in a digital (on/off) manner, resulting from variations in transcriptional activity or gene accessibility (25,26), the numbers and dynamic expression of signaling receptors (e.g., CD8, IL-2R), and regulators of both positive and negative feedback loops (e.g., ERK, SHP-1, and RAS) (23,30,38,39). Expression of IL-2 and IFN-γ in human CD4 + T cells has also been shown to depend on the categorical translocation of the transcription factor NFATc2 (24).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the activation of individual T cells does not occur homogeneously upon stimulation-even isogenic ones-but rather activate in a digital (on/off) manner, resulting from variations in transcriptional activity or gene accessibility (25,26), the numbers and dynamic expression of signaling receptors (e.g., CD8, IL-2R), and regulators of both positive and negative feedback loops (e.g., ERK, SHP-1, and RAS) (23,30,38,39). Expression of IL-2 and IFN-γ in human CD4 + T cells has also been shown to depend on the categorical translocation of the transcription factor NFATc2 (24).…”
Section: Discussionmentioning
confidence: 99%
“…IL-2 receptor activation leads to reduced expression of IL-2, restricting autocrine stimulation, while levels of IL-2Ra remain high for continued paracrine surveillance (Smith and Popmihajlov 2008;Crispin and Tsokos 2009). Depending on co-receptor stimuli, activated T cells proliferate and undergo commitment into CD4þ (helper, Th) or CD8þ (cytotoxic T lymphocyte, Tc) (Williams and Bevan 2007;Busse et al 2010). The level of IL-2 signaling has also been shown to affect the development of non-terminally differentiated (quiescent) CD4þ and CD8þ memory cells, which are necessary for effective immune recall upon reinfection.…”
Section: Ligand and Receptor Biologymentioning
confidence: 99%
“…The modeling of biochemical pathways involved in the regulation of the inflammatory response has been addressed in many papers during the past decade (74)(75)(76)(77)(78). Further, in the past few years several studies have adopted this approach to address some aspects of the molecular basis of asthma.…”
Section: Data-driven Mathematical Modeling Of Biochemical Networkmentioning
confidence: 99%
“…Also, using elegant single-cell measurements and modeling, Podtschaske et al showed that graded T-cell receptor signaling results in graded activation of the transcription factor nuclear factor κB, but a digital activation of transcription factor NFATc2 results in a switch that regulates the number of T lymphocytes actively participating in an immune response (82). In addition, cytokines such as IL-2, which have different effects on different populations of T lymphocytes, have also been studied by combined experimentation and modeling approaches specifically addressing the spatiotemporal complexity (75).…”
Section: Data-driven Mathematical Modeling Of Biochemical Networkmentioning
confidence: 99%